Toxonomia de Dissomphalus (Hymenoptera, Bethylidae) do Panamá - Brito, Chirlei Dias de (2017)
The Panama fauna of Dissomphalus is studied and sixty-four species are recognized, 31 are descibed and illustrated as new to Science: D. sp. 1, D. sp. 3, D. sp. 2, D. sp. 4, D. sp. 5, D. sp. 6, D. sp. 7, D. sp. 8, D. sp. 9, D. sp. 10, D. sp. 11, D. sp. 12, D. sp. 13, D. sp. 14, D. sp. 15, D. sp. 16, D. sp. 17, D. sp. 18, D. sp. 19, D. sp. 20, D. sp. 21, D. sp. 22, D. sp. 23, D. sp. 24, D. sp. 25, D. sp. 26, D. sp. 27, D. sp. 28, D. sp. 29, D. sp. 30 and D. sp. 31. Nine species are recorded for the first time from Panama: D. angulatus, D. galeatus, D. hirtus, D. infissus, D. personatus, D. pilus, D. politus, D. pronus and D. vallensis. Sixteen had their geographic distribution data broadened: D. bilobatus, D. brasiliensis, D. cervoides, D. coronatus, D. curvifoveatus, D. geniculatus, D. gilvipes, D. guttus, D. intradentatus, D. plaumanni, D. piscicercus, D. punctatus, D. rettenmeyeri, D. rufipalpis, D. strepsus and D. unitus. And eight species previosly recorded from Panama, were not found in the study material: D. altivolans, D. apertus, D. culteratus, D. declinatus, D. latus, D. ramosus, D. strabus and D. subdeformis. A key for Central American species of Dissomphalus is included.